NUMERICAL RESEARCH OF THE MOISTURE CONDENSATION ELIMINATION IN THE CABIN OF THE UNIFIED TECHNOLOGICAL ELECTRIC TRANSPORT VEHICLE - N. M. Filkin; A. M. Tatarkin (Вестник СибАДИ, 2018)
Introduction. This article deals with the problem of moisture condensation inside the cabin of the technological electric transport vehicle. The hypothesis of using the forced air ventilation in the cabin is substantiated, by which such problem could be solved.Materials and methods. The article describes the application of the ANSYS Fluent Software Package to assess the effect of the location and shape of the ducts on the ventilation process inside the cabin. Accordingly, the key stages of air flow modeling in this program are considered.Results. The main content of the research is to analyze the modeling airflow process in the cabins with a different configuration of inlet and outlet nozzles. Therefore, basing on the analysis of the obtained airflow velocity contours, the conclusion is made about the rational arrangement of the inlet and outlet channels.Discussion and conclusions. The conclusion is made about the necessity of the further research that would refer to creating a three-dimensional model of the cabin. The results of the research as well as resolutions are taken into account.